The faithfulness of atomic polymorphism - Ferreira, Fernando (2014)
It is known that the full intuitionistic propositional calculus can be embedded into the atomic polymorphic system Fat, a calculus with only two connectives: the conditional and the second-order universal quantifier. The embedding uses a translation of formulas due to Prawitz and relies on the so-called property of instantiation overflow. In this paper, we show that the previous embedding is faithful i.e., if a translated formula is derivable in Fat, then the original formula is already derivable in the propositional calculus.